Understanding team resilience in the world's best athletes: A case study of a rugby union World Cup winning team - Morgan, P. B. C.; Fletcher, D.; Sarkar, M. (Psychology of Sport and Exercise, 2015)
Objective: Although team resilience research has identified the characteristics of elite sport teams that positively adapt to adversity, further research is required to understand how resilient teams function. The objective of this study, therefore, was to explore the psychosocial processes underpinning team resilience in elite sport. Design: Narrative inquiry was employed to better understand team resilience. Method: The sample consisted of eight members of the 2003 England rugby union World Cup winning team. The autobiographies of these team members were analyzed using three types of narrative analyzes: holistic-content analysis, holistic-form analysis, and categorical-form analysis. Results: Findings revealed five main psychosocial processes underpinning team resilience: transformational leadership, shared team leadership, team learning, social identity, and positive emotions. An examination of narrative structure within the autobiographies revealed a progressive narrative form characterized by a collective positive evaluation of setbacks. Conclusions: This study extends previous team resilience research by going beyond the identification of resilient characteristics to explaining underpinning psychosocial processes. The team resilience processes are discussed in relation to previous research findings and in terms of their implications for practising sport psychologists. It is anticipated that this study will provide practitioners with a framework to develop team resilience at the highest levels of sport.